Sovereign grace : the place and significance of Christian freedom in John Calvin's political thought - Stevenson, William R. (Oxford University Press, 1999)
The Reformation thinker John Calvin had significant and unusual things to say about life in public encounter, things which both anticipate modern thinking and, says William Stevenson, can serve as important antidotes to some of modern thinking's broader pretensions. This study attempts to give a coherent picture of Calvin's political theory by following the stream that flows from his fascinating short essay, "On Christian Freedom," one chapter in the magisterial Institutes of the Christian Religion. Stevenson argues that a full examination of this essay yields not only a more thoroug.